Efficiency improvement and NOx emission reduction potentials of two-stage turbocharged Miller cycle for stationary natural gas engines - Kesgin, U (JOHN WILEY & SONS LTD, 2005)
As a part of an engine research and development project in cooperation with industry, a V20 engine is designed with two-stage high-pressure turbocharging, and the potential of the Miller cycle is examined through calculations using computational models based on experimental as well as computational studies. The stationary gas engines must produce less than 250 mg Nm(-3) in 5% excess of O-2, additionally the amount of NOx emissions and their dependence on engine operational and design conditions are investigated by using a zero-dimensional reaction kinetic model. The results show an increase in efficiency, also the amount of NOx emissions is kept under the constraint value of 250 mg Nm(-3) for stationary engines. The results obtained here promise a very high improvement potential for future emission regulations. Copyright (C) 2004 John Wiley Sons, Ltd.
Keywords: two-stage turbocharged Miller cycle; gas engine; efficiency; NOx emissions; Energy & Fuels; Nuclear Science & Technology